Modern Women, Modern Work : Domesticity, Professionalism, and American Writing, 189-195 - Sawaya, Francesca (Book collections on Project MUSE., 2004)
Focusing on literary authors, social reformers, journalists, and anthropologists, Francesca Sawaya demonstrates how women intellectuals in early twentieth-century America combined and criticized ideas from both the Victorian "cult of domesticity" and the modern "culture of professionalism" to shape new kinds of writing and new kinds of work for themselves. Sawaya challenges our long-standing histories of modern professional work by elucidating the multiple ways domestic discourse framed professional culture. Modernist views of professionalism typically told a racialized story of a historical break between the primitive, feminine, and domestic work of the Victorian past and the modern, masculine, professional expertise of the present. Modern Women, Modern Work historicizes this discourse about the primitive labor of women and racial others and demonstrates how it has been adopted uncritically in contemporary accounts of professionalism, modernism, and modernity. Seeking to recuperate black and white women's contestations of the modern professions, Sawaya pairs selected novels with a broad range of nonfiction writings to show how differing narratives about the transition to modernity authorized women's professionalism in a variety of fields. Among the figures considered are Jane Addams, Ruth Benedict, Willa Cather, Pauline Hopkins, Zora Neale Hurston, Sarah Orne Jewett, Josephine St. Pierre Ruffin, and Ida Tarbell. In mapping out the constraints women faced in their writings and their work, and in tracing the slippery compromises they embraced and the brilliant adaptations they made, Modern Women, Modern Work boldly reenvisions the history of modern professionalism in the United States.